PERANAN TIK-TOK @VMULIANA DALAM MEMENUHI KEBUTUHAN INFORMASI PEKERJAAN FOLLOWERS - Supriadi, Supriadi; Octaviansyah, Nala; Sumiyati, Sumiyati (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM Azramedia indonesia, 2024)
Social media is classified as new media in the mass media group. The purpose of the study was to determine the role of the @Vmuliana account in fulfilling job information needs. The research method is a descriptive survey method with a quantitative approach. The sampling technique used simple random sampling. The results showed (1) the Tiktok @Vmuliana account as media has a big role in fulfilling user information needs. (2) @Vmuliana account can function as an information media according to the needs of the audience, so that users feel satisfied after using @Vmuliana account. (3) Socio-psychological factors (seeking job information) encourage followers to use the @Vmuliana account as a medium for information about job vacancies. (3) The information in the @Vmuliana content is considered varied and easy for followers to understand. (4) The credibility of the information is based on Vina Muliana's work experience which is explained in detail and structured. (5). Interest in information is shown by positive feedback from followers, comments, likes, shares, and many reposts. This shows that followers like the content as an addition to job knowledge.